2023
DOI: 10.1002/anie.202218743
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Oxycyanation of Alkenes with Sulfonyl Cyanide

Abstract: Oxycyanation of alkenes would allow the direct construction of useful β-hydroxy nitrile scaffolds. However, only limited examples of such reactions have been reported, and some problems including limited substrate scope and the lack of diastereocontrol in the case of the oxycyanation of internal alkenes have arisen. We herein report on the intermolecular oxycyanation of alkenes using p-toluenesulfonyl cyanide (TsCN) in the presence of tris(pentafluorophenyl)borane (B(C 6 F 5 ) 3 ) as a catalyst, affording prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, when the mixture was analyzed by 13 C NMR spectroscopy, a downfield shift in the signal corresponding to the cyano group (δ = 75.6 ppm for BrCN to 84.0 ppm for BrCN·B­(C 6 F 5 ) 3 ) was observed (Scheme a). These distinct trends are consistent with the coordination of the cyano group of ICN to the boron center of B­(C 6 F 5 ) 3 , , which strongly suggests that BrCN has a similar coordination mode. A significant upfield shift in the signal corresponding to the boron center of B­(C 6 F 5 ) 3 (δ = 58.9 ppm for B­(C 6 F 5 ) 3 to −4.7 ppm for BrCN·B­(C 6 F 5 ) 3 ) provides an additional support for the coordination. , …”
supporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, when the mixture was analyzed by 13 C NMR spectroscopy, a downfield shift in the signal corresponding to the cyano group (δ = 75.6 ppm for BrCN to 84.0 ppm for BrCN·B­(C 6 F 5 ) 3 ) was observed (Scheme a). These distinct trends are consistent with the coordination of the cyano group of ICN to the boron center of B­(C 6 F 5 ) 3 , , which strongly suggests that BrCN has a similar coordination mode. A significant upfield shift in the signal corresponding to the boron center of B­(C 6 F 5 ) 3 (δ = 58.9 ppm for B­(C 6 F 5 ) 3 to −4.7 ppm for BrCN·B­(C 6 F 5 ) 3 ) provides an additional support for the coordination. , …”
supporting
confidence: 77%
“…Tris(pentafluorophenyl)borane, B(C 6 F 5 ) 3 , is widely used as a strong Lewis acid in organic synthesis . It can efficiently activate a cyanating reagent through the coordination of the cyano group to the boron center, allowing for an electrophilic cyanation that is otherwise difficult to achieve using other Lewis acids. , Our group reported that the use of B(C 6 F 5 ) 3 catalyst permits the electrophilic cyanation of silyl enol ethers and alkenes to be achieved . Inspired by these previous studies on electrophilic cyanation, we hypothesized that the use of B(C 6 F 5 ) 3 that can efficiently activate cyanogen halides would enable the practical halocyanation of alkenes with the readily available BrCN.…”
mentioning
confidence: 99%
“…The results of this optimization were presented in Table 1. Based on a report by Satoshi Minakata, 43 tris( pentafluorophenyl)borane (B(C 6 F 5 ) 3 ) could activate TsCN through coordination of the cyano group to the boron center, making the cyano carbon center more electrophilic that could be attacked by an alkene. Sulfoxonium ylides are versatile zwitterionic compounds, and we hypothesized that the nucleophilic α-carbon of β-ketosulfoxonium ylides could undergo an electrophilic cyanation process as well.…”
Section: Resultsmentioning
confidence: 99%
“…25–29 Most of the traditional cyanating reagents like metallic cyanides and TMSCN are highly toxic and environment-unfriendly. Recently, safe and effective p -toluenesulfonyl cyanide (TsCN) has been successfully employed in the cyanation of various compounds, such as 1,3-dicarbonyl compounds, 30 β-keto esters, 30 tetrahydroisoquinolines, 31 adamantane derivatives, 32,33 arenes, 34,35 alkenes, 36 and boron enolates (Scheme 2b). 37,38…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation